Reinternações no Hospital Estadual Bauru: ocorrência e possíveis causas - Merli, Ana Paula Delgallo; Lopes, Eymar Sampaio; Macharelli, Carlos Alberto [UNESP] (My University, 2013)
Hospitalizations consist of traumatic procedures for the patients, beyond representing high social cost for the family and the society. For the hospital institutions these programmed reinternações do not represent an additional cost that overload the system financial of the institution, either state or particular it. A significant number of these internments/reinternações could possibly be prevented with one better understanding of the conditions after-high. The present study with objective was proceeded to evaluate the number of reinternações in a public hospital and to identify the reasons of its occurrence. The data had been collected next to the hospital institution, through documents, registers and interviews next to the patients. The results are based on 205 patients who had suffered to readmission not programmed in the period from January the July of 2006, the general percentage of reinternações in the studied period was 3.1%. They also show that, although the patients to receive recommendations on the cares to be taken in house, exist little observance to the same ones.

Las hospitalizaciones son procedimientos traumáticos para los pacientes, más allá de representar el alto coste social para la familia y la sociedad. Para las instituciones hospitalarias, estatal o particular estas readmisiones no programadas representan un coste financiero adicional. Un número significativo de estas internaciones/readmisiones se podía prevenir posiblemente con una comprensión mejor de las condiciones después-altas. El actual estudio tuve como objetivo evaluar el número de readmisiones en un hospital público, y identificar las razones de su ocurrencia. Los datos fueron colectados en la institución hospitalária, a través de documentos, registros y entrevistas con los pacientes. Los resultados se basan en 205 pacientes que habían sufrido la readmisón no programada en el período de enero al julio de 2006, en un total de 3.1% de las internaciones. También se mostró que, aunque los pacientes reciban recomendaciones en los cuidados de ser tomado en su casa, hay poca observancia a cerca de las mismas.

As hospitalizações constituem-se de procedimentos traumáticos para os pacientes, além de representarem alto custo social para a família e para a sociedade. Para as instituições hospitalares, estatal ou particular essas reinternações não programadas representam um custo financeiro adicional. Um número significativo dessas internações/reinternações possivelmente poderia ser evitado com uma melhor compreensão das condições pós-alta. O presente estudo teve como objetivo avaliar o número de reinternações num hospital público e identificar as razões de sua ocorrência. Os dados foram coletados junto à instituição hospitalar, através de documentos, registros e entrevistas junto aos pacientes. Os resultados são baseados em 205 pacientes que sofreram reinternação não programada no período de janeiro a julho de 2006, num total de 3,1% das internações. Mostram também que, apesar de os pacientes receberem recomendações sobre os cuidados a serem tomados em casa, existe pouca observância sobre as mesmas.
Keywords: Patient readmission; Economics hospital; Medical records department hospital; Readmisión del paciente; Economía hospitalaria; Servicio de registros médicos en hospital; Readmissão do paciente; Economia hospitalar; Serviço hospitalar de registros médicos